The Relationship between Parity and the Intensity of Pain from Cesarean Section Surgery at Datoe Binangkang Regional General Hospital, Bolaang Mongondow Regency - Martini Eka Puspawati M. Sujani; Reny Retnaningsih (Jurnal Ventilator, 2025)
Cesarean section is a widely used surgical delivery procedure, with increasing prevalence globally and nationally, often accompanied by postoperative wound pain. Unmanaged pain can delay recovery, hinder early mobilization, and lower the quality of postpartum care. Various clinical and obstetric factors influence pain intensity after cesarean section, one of which is parity. However, scientific evidence regarding the relationship between parity and cesarean section wound pain, particularly in regional hospitals in Indonesia, remains limited. This study aimed to explore the relationship between parity and the intensity of cesarean section wound pain in post-cesarean section mothers at Datoe Binangkang Regional General Hospital in Bolaang Mongondow Regency. Using an observational analytical design with a cross-sectional approach, the study involved 50 post-cesarean mothers selected through total sampling. Parity was categorized into primipara, multipara, and grandemultipara, and the intensity of surgical wound pain was measured using the Visual Analog Scale (VAS), classified into mild, moderate, and severe pain. Data analysis was conducted univariately and bivariately using Spearman’s rank correlation test. The results revealed a statistically significant relationship between parity and postoperative pain intensity, with a weak positive correlation. The study concluded that parity influences pain intensity, though not as a dominant factor. These findings highlight the importance of considering parity in planning individualized and evidence-based pain management for cesarean section patients.